2014
DOI: 10.1080/17461391.2014.932016
|View full text |Cite
|
Sign up to set email alerts
|

Sleep/wake behaviours of elite athletes from individual and team sports

Abstract: Sleep is an essential component for athlete recovery due to its physiological and psychological restorative effects, yet few studies have explored the habitual sleep/wake behaviour of elite athletes. The aims of the present study were to investigate the habitual sleep/wake behaviour of elite athletes, and to compare the differences in sleep between athletes from individual and team sports. A total of 124 (104 male, 20 female) elite athletes (mean ± s: age 22.2 ± 3.0 years) from five individual sports and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
212
7
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(241 citation statements)
references
References 53 publications
19
212
7
3
Order By: Relevance
“…A study in 47 Olympic athletes from various sports documented an average of 6.9 h of sleep across four nights, as measured objectively by actigraphy [21]. A similar amount of sleep was found in 124 elite Australian athletes from both individual and team sports, with team athletes averaging 6.8 h and athletes from individual sports averaging 6.5 h of sleep per night [22]. Research in Australian Olympic swimmers found that during early morning training days, athletes obtained just 5.4 h of sleep on average, compared to 7.1 h of sleep on rest days [23].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A study in 47 Olympic athletes from various sports documented an average of 6.9 h of sleep across four nights, as measured objectively by actigraphy [21]. A similar amount of sleep was found in 124 elite Australian athletes from both individual and team sports, with team athletes averaging 6.8 h and athletes from individual sports averaging 6.5 h of sleep per night [22]. Research in Australian Olympic swimmers found that during early morning training days, athletes obtained just 5.4 h of sleep on average, compared to 7.1 h of sleep on rest days [23].…”
Section: Introductionmentioning
confidence: 80%
“…The recommended amount of sleep for adults is between 7 h and 9 h per day [20]. According to the available evidence, many athletes may not meet the minimum sleep quantity recommendation [21][22][23]. A study in 47 Olympic athletes from various sports documented an average of 6.9 h of sleep across four nights, as measured objectively by actigraphy [21].…”
Section: Introductionmentioning
confidence: 99%
“…33 Interestingly, data from elite endurance athletes have frequently shown reductions in sleep quantity the night prior to competition. 34 Perceived ratings of sleep were not measured the night prior to matches in the present study and therefore a reduction may have occurred. Future work is required in order to further understand the effects of training and match load on perceived and objective measures of sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…As it is non-invasive and allows data collection over significant periods of time at home or while travelling, actigraphy is particularly useful for understanding sleep patterns among athletes [4]. Four main studies have examined the amount and quality of sleep that elite athletes obtain [28][29][30][31]. Specifically, there is limited scientific information regarding sleep requirements and characteristics in elite soccer players.…”
Section: Sleep and Recoverymentioning
confidence: 98%